An Empirical Study of Nifty 50 Option Time Spreads - Slivka, Ronald T.; Liang, Yuxing; Xue, Jieqi (Indian Journal of Finance, 2020)
The objective of this study was to identify and test preliminary rules for trading call option time spreads and then to assess opportunities for further research to improve on those rules. To do so, the theoretical and empirical properties of near-the-money time spreads were used to develop four rules for profitably trading in India’s Nifty 50 (NSE 50) call options. Day-end pricing for 2015 – 2019 included periods of rising, falling, and stable volatility. The resulting four rule algorithm produced positive results on out-of-sample data and outperformed a buy and hold strategy. As the general procedure followed for rule development was not country specific, it was applied to options on China’s SSE 50 index, where the algorithm was found to outperform a hold-to-expiry strategy in every year tested. These related studies of NSE 50 and SSE 50 option time spreads provide a helpful addition to the growing knowledge about the developing derivatives markets in India and China. Opportunities for further research are described.